Revolusi Kopernikan Ala Immanuel Kant - Moh Tamtowi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
The history of western philosophy is coloured by a long debate between  rationalism and empiricism. Immanuel Kant then came to synthesise the very  contradictive thought. Kant tried to establish a philosophical system to overcome  extremities of both rationalism and empiricism. The effort was to differentiate  knowledge produced by rationalism from empiricism. Experience, which is the  source of knowledge from empiricism perspective, produces a new knowledge  (synthesis), but it is not in general knowledge. While ratio is capable of building a  general knowledge (analytic), but it is unable to produce a new one. This is how  the idea of “synthesis a priori” comes to emerge. This kind of thought is known as  transcendental philosophy.